High Yield Epoxidation of Fatty Acid Methyl Esters with Performic Acid Generated in situ - Campanella, Alejandrina (2008)
The impact of the relevant process variables on the reaction of soybean oil fatty acid methyl esters with performic acid (PFA) generated in situ using concentrated hydrogen peroxide (up to 60 wt%), to produce an epoxidized product in high yield, is studied in detail. The degree of mixing, temperature, concentration and molar ratios of reactants and/or use of a diluent were considered. Temperature increases are significantly detrimental for achieving high oxirane numbers, as the selectivity to ring-opening reactions increases. Higher concentrations of either formic acid or H2O2 are also harmful (particularly, the carboxylic acid) but much less than temperature. A proposed alternative process, employing moderate temperature (up to 40 ?C) and concentrated H2O2, compares favourably with the conventional one; higher conversion combined with high epoxide productivity and selectivity are attainable. Using economically sound reactants molar ratios, under well-mixed regimes, in which the immiscible polar and organic phases are well dispersed, the epoxidation process can be adequately described using an (equilibrated) two-phase reaction model. The model accounts for both the reversible peracid formation (in the aqueous phase) and the epoxidation reaction proper, together with the attacks on the epoxide ring by formic acid and performic acid (in the organic phase).